A Cost Effective Region Specific Spatial Domain Color Image Watermarking Scheme - Phadikar, Amit; Maity, Santi P.; Verma, Bhupendra; Jain, Sanjeev (INFOCOMP Journal of Computer Science, 2008)
In object oriented images, ROI (Region of Interest) is an area which contains important information and attracts more attention of an image viewer. So it is desirable to embed robust watermark in ROI to give better protection. The present paper describes a region specific low cost (computational complexity) watermarking scheme in spatial domain by inserting data into the most valuable regions in the cover image. Those regions are selected by Quad tree decomposition of host image. Quad tree decomposition is a method of image segmentation which splits an image into regions such that large regions are formed when the intensities are uniform and small regions of variable sizes are created, in the comparatively non-uniform area of the image. Small regions represent the presence of critical information of the image, and hence are the important places of watermarking. Simulation results duly support this claims.